Beach tennis injuries: a cross-sectional survey of 206 elite and recreational players - Berardi, M.; Lenabat, P.; Fabre, T.; Ballas, R. (The Physician and Sportsmedicine, 2020)
Objectives: Although a million people regularly play beach tennis (BT) through the world there is no published information on BT injuries. The aim of this study was to describe the epidemiology of BT injuries, and to identify differences between injured and non-injured players. Methods: This was a retrospective cross-sectional epidemiology study of 206 BT players from Réunion Island describing the injuries occurring in BT. A questionnaire was developed to capture the type and chronicity of the injuries they had suffered over the prior three years. Comparisons were made between elite, regional and recreational players. Results: There were 178 injuries in 92 players (44.7%), which was an incidence of 1.81 injuries per 1000 hours of play. There were 77 acute injuries (23.8% of players, incidence of 0.78 injuries/1000 hrs.) and 101 chronic injuries (30.6% of players, incidence of 1.03 injuries/1000 hrs.). The shoulder was the most frequently injured area. The main upper limb injuries were chronic tendinopathy while most acute injuries occurred in the lower limbs. The incidence of lateral epicondylitis at the elbow was 0.36 per 1000 hours of play, or a prevalence of 4.2%. The incidence of injuries in elite players was less than that in non-ranked players (1.71 vs 2.04 injuries/1000 hours play). Recreational players more often had chronic injuries (p < 0.001). Conclusion: Information about musculoskeletal injuries is invaluable for healthcare professionals involved in the care of athletes. Such knowledge can be used to guide the medical surveillance of athletes and to help develop injury prevention strategies.